Karakterens opløsning i diskursen: fra Gertrude Stein til René Pollesch - Schultz, Laura Luise (Peripeti, 2021)
In her reflections on the status of the subject in the postdramatic theatre, Laura Luise Schultz aims to show how the experimental writing of Gertrude Stein can be traced to the practice of contemporary playwrights such as René Pollesch.